Etude du nerf phrenique chez le cobaye (Cavia porcellus, L., 1756) - Salgado, M. C B; Orsi, A. M.; Vicentini, Carlos Alberto [UNESP]; Mello Dias, S. (My University, 1983)
The aim of the present study to ascertain the mode of origin of the phrenic nerve and to provide a morphological basis for experimental studies of this nerve in the guinea pig. In sketches made of the dissections, in 10 male and 10 female guinea pigs adults, the modes of origin of the phrenic roots were demonstrated to arise from the fourth to the seventh cervical nerves. Four types of origin could be distinguished. The phrenic nerve of the guinea pig has three or four roots.
Study of the phrenic nerve in the guinea pig (Cavia porcellus, L., 1756)
Keywords: cervical nerve; diaphragm; guinea pig; nerve root; nervous system; nonhuman; peripheral nervous system; phrenic nerve; animal; female; histology; male; spinal root; Animal; English Abstract; Female; Guinea Pigs; Male; Phrenic Nerve; Spinal Nerve Roots